The Strategy of School Heads To Improve The Quality of Learning in 7 State Basic Schools in Kecamatan Air Kumbang - Nabila, Putri; Fitria, Happy; Wahidy, Achmad (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to identify and describe the Principal's Strategy for Improving the Quality of Learning in SD Negeri 7 Air Kumbang District. The method used is a qualitative method. Data collection techniques using observation, interviews and documentation. The results of this study can be concluded that the principal at SD Negeri 7 Air Kumbang has an obligation to strive so that all the potential in his institution can be utilized as well as possible in order to achieve the expected improvement in learning. The various strategies undertaken by the principal in order to improve the quality of learning at SD Negeri 7 Air Kumbang include (a). Improvement of Teacher Teaching Ability, (b). Optimizing the Use of Media and Educational Facilities, (c). Implementation of Routine Supervision, (d). Collaborating with the Community and (e). Strict Application of Discipline. All of the principal strategies above can work well because the stakeholders in SD Negeri 7 Air Kumbang work together to improve the quality of learning. All of the strategies implemented by the principal can work well because the stakeholders in SD Negeri 7 Air Kumbang work together to improve the quality of learning